Kepemimpinan Pastoral Bercorak Pastor-Sentris Dalam Perspektif Teologi - Silvester Manca (Jurnal Alternatif Wacana Ilmiah Interkultural, 2020)
Leadership is an important aspect of Church life. In fact, the style of leadership that are carried out in the Church must reflect the teachings of faith and theology as well as the basic principles in the Church. It must not conflict with the basic spirit of the Church. With that, the meaning of Church presence as sacrament of salvation in the middle of the world becomes clear and felt. In this article, it is emphasized that the surviving pastoral-centric style of leadership in the Church is not problematic in the context of pastoral management, but also contradicts the theology and the principle of Church social teaching. At the very least, this leadership contradicts the nature of the Church as communion or fellowship, the principles of participation and subsidiarity and the nature of the ministerial priesthood. Therefore, such leadership must be rejected.